STRENGTHENING CHARACTER, ETHICS AND DIGITAL LITERATURE DURING THE COVID-19 PANDEMIC: PENGUATAN KARAKTER, ETIKA DAN LITERASI DIGITAL PADA MASA PANDEMI COVID 19 - Susi Sih Kusumawardhany; Yunita Kurnia Shanti; Sudarmadi Sudarmadi (ASOSIASI IDEBAHASA KEPRI, 2023)
Character education is something that absolutely must be implemented because basically all teachers as educators have the same goal in shaping the nation's character. Character education is not necessarily the responsibility of moral education or character and Pancasila education, but is the responsibility of all fields of study. Therefore, in the 2013 implementation curriculum, the balance of learning domains between cognitive, affective, and psychomotor is an absolute output as part of national character education. Character is a person's character or morals obtained from internalization with their environment. A person's character will be good if it is based on moral and ethical values that apply and are agreed upon in society. Emphasized the importance of three components of good character, namely moral knowledge or moral knowledge, moral feelings or feelings about morals, and moral actions or moral actions. Good character will appear after the three character components can be fulfilled in students. The purpose of this service is to strengthen character, ethics and digital literacy in the Covid 19 pandemic situation. So this service is moved to provide reinforcement to schools so that they can help and facilitate the use of digital literacy. The method we use is to provide training to schools on how to use literacy easily. Because the result of the learning process is student character development, in reality online learning is carried out by each school only for student cognitive development. Students are only given assignments and the teacher explains their respective subjects, without asking whether students have bathed or students are already in a suitable place for learning, even though the task of a teacher is not only to build students' cognitive development but also to be able to build and instill values. Good personality traits for students and that is part of the main task of a true educator.